2021
DOI: 10.2106/jbjs.21.00166
|View full text |Cite
|
Sign up to set email alerts
|

MOON’s Strategy for Obtaining Over Eighty Percent Follow-up at 10 Years Following ACL Reconstruction

Abstract: The Multicenter Orthopaedic Outcomes Network (MOON) study of anterior cruciate ligament (ACL) reconstruction has achieved >80% follow-up for study subjects who were enrolled from 2002 to 2005; patient-reported outcome measures (PROMs) were reported at 2, 6, and 10 years through a carefully designed protocol that included surgeon involvement to encourage subjects to complete and return questionnaires. The process included emails and telephone calls from the central coordinating center, from research coordinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Possible explanations may involve the associated time burden, particularly significant for ACLR patient cohorts who are typically young and busy. It is well recognised that lengthy questionnaires can lead to respondent fatigue, resulting in less thoughtful answers or premature termination of their participation [19,15,18,36]. Among national ligament registries, the NLR is unique in its collection of four subjective PROMs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations may involve the associated time burden, particularly significant for ACLR patient cohorts who are typically young and busy. It is well recognised that lengthy questionnaires can lead to respondent fatigue, resulting in less thoughtful answers or premature termination of their participation [19,15,18,36]. Among national ligament registries, the NLR is unique in its collection of four subjective PROMs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Marx activity scale has been shown to be reliable with good concurrent and divergent validity, it is not without its own weaknesses. 20 For example, among patients recovering from ACLR, lower activity scores may be the consequence of life choices made because of a fear of reinjuries or an avoidance of future symptoms rather than specific symptoms related to pain, instability, and/or overall function. 8 Thus, decrements in activity levels relevant to baseline values may not be solely related to the variables of interest, which then has the potential to obscure the accuracy of predictive modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies published by the Multicenter Orthopaedic Outcomes Network (MOON) group have noted modest rates of return to preinjury activity levels that generally are not sustained over longer-term periods. 6,7,9,12 Of note, the MOON group has largely based its assessments of return to preinjury activity levels on changes in the Marx activity scale score, a tool that evaluates decelerating and pivoting activities during a patient’s “healthiest and most active state in the past year.” 20 Additionally, the instrument is designed to avoid ceiling effects, as a score of 12 to 16 generally denotes a high level of activity that would be typical of participation in competitive cutting- and pivoting-type sporting activities: for example, high school and collegiate sports. Based on a consensus opinion, a 2-point decrease in the preinjury versus postinjury score constitutes a substantial negative change that indicates an inability to return to preinjury function.…”
mentioning
confidence: 99%
“…What we learned the most from this study were the obstructions to conducting it. Although several authors have reported much higher response rate or made recommendations as to methods of contacting former patients, [11][12][13][14] those methods are either out of date or not applicable to the type of study we were trying to conduct. Current IRB and Health Insurance Portability and Accountability Act (HIPAA) patient-confidentiality requirements severely restrict recruitment efforts, particularly by phone.…”
Section: Discussionmentioning
confidence: 99%
“…The Authors of the Multicenter Orthopedic Outcomes Network (MOON) study 13 in 2021 reported successfully contacting 80% of a cohort of 516 patients 10 years after anterior cruciate ligament (ACL) reconstruction. They emphasized the importance of regular contact by a committed investigator making contact with the subjects, including the treating surgeon if necessary.…”
Section: Discussionmentioning
confidence: 99%